2003
DOI: 10.1159/000071825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Riluzole on MK-801 and Amphetamine-Induced Hyperlocomotion

Abstract: N-methyl-D aspartate (NMDA) antagonists, such as MK-801, and the dopamine indirect agonist amphetamine are pharmacological models used for the evaluation of putative new treatments for schizophrenia. Since the psychotomimetic effects of NMDA antagonists have recently been linked to their ability to increase glutamate release and since the glutamate release inhibitor riluzole prevented NMDA antagonist neurotoxicity, we evaluated the effect of riluzole on hyperlocomotion induced by MK-801 (0.25 mg/kg) and amphet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition to the clinical evidence, animal studies have shown that long-term use of riluzole induces antidepressant- and antimanic-like behaviors in rodents 96,97. It is important to note, however, that despite its efficacy, no evidence suggests that riluzole acts more rapidly than existing antidepressants, though it may be a reasonable therapeutic option in treatment-resistant cases.…”
Section: Riluzole and Ketamine: Prototypes For New Improved Glutamatmentioning
confidence: 99%
“…In addition to the clinical evidence, animal studies have shown that long-term use of riluzole induces antidepressant- and antimanic-like behaviors in rodents 96,97. It is important to note, however, that despite its efficacy, no evidence suggests that riluzole acts more rapidly than existing antidepressants, though it may be a reasonable therapeutic option in treatment-resistant cases.…”
Section: Riluzole and Ketamine: Prototypes For New Improved Glutamatmentioning
confidence: 99%
“…Riluzole has not yet been studied in the manic phase of BPD, although it purportedly reduced hyperactivity caused by amphetamine in an animal model of mania [54]; these data suggest that riluzole should be considered for further testing in other phases of BPD.…”
Section: Glutamate Releasementioning
confidence: 99%
“…Riluzole also enhances glutamate reuptake and activates synthesis of neurotrophins [108, 109]. Interestingly, one preclinical study found that pretreatment with 10 mg/kg riluzole (but not 3 mg/kg) moderately reduced amphetamine-induced hyperlocomotion [110], which could suggest potential antimanic efficacy.…”
Section: Introductionmentioning
confidence: 99%